Protective effects of prebiotic (resistant maltodextrin) and silymarin against toxicity of carbon tetrachloride in liver rat and kidney - G. A. EL. SAYED, M.; A. H. FARAG, ENAS.; M. Nasr, HEBA. (International Journal of Pharmacology and Toxicology, 2020)
Exposure to carbon tetrachloride induces acute and chronic hepatic injuries as well as renal injuries in rats. Therefore, the current study aimed to evaluate the protective role of prebiotic (digestion resistant maltodextrin) and silymarin against carbon tetrachloride -induced heptorenal toxicity in albino rats. Six groups with ten rats each were used for this purpose; these groups included the control vehicle group that received saline daily for 30 days, prebiotic group (1g/kg, orally) daily for 30 days; silymarin group (200 mg/kg orally) daily for 30 days; carbon tetrachloride group (2.5ml/kg intraperitoneally twice per week for three week; the prebiotic – carbon tetrachloride group; the silymarin – carbon tetrachloride group. The results revealed that carbon tetrachloride significantly increased serum levels of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, total bilirubin cholesterol, triglyceride, urea and creatinine. In addition, there were substantial increase in lipid peroxidation (malondialdehyde) and level of glucose with significant decreases in albumin, total protein, creatinine kinase, hemoglobin and red blood cells. Carbon tetrachloride also caused histological changes in liver and kidney tissues. However, administration of prebiotic and silymarin alone ameliorated the carbon tetrachloride induced liver and kidney damage with improved hematological, lipid profile and glucose level.
Keywords: Use about five key words or phrases in alphabetical order; Separated by Semicolon.